Ecotherapy – A Forgotten Ecosystem Service: A Review - Summers, James K.; Vivian, Deborah N. (Frontiers in Psychology, 2018)
Natural ecosystems perform fundamental life-support services upon which human civilization depends. However, many people believe that nature provides these services for free and therefore, they are of little or no value. One nearly forgotten ecosystem service is ecotherapy – the ability of interaction with nature to enhance healing and growth. While we do not pay for this service, we pay significantly for its loss resulting in slower recovery times, greater distress, reduced well-being and losses in those images of nature that contribute to our basic happiness. Little is understood about the ecotherapy benefits of the natural environment and its ecosystem services. The complex and interactive relationship of ecosystems, their services and human well-being is poorly acknowledged in the broad social, philosophical and economic well-being literature. In this article, we examine the role of nature and its ecosystem services in ecotherapy and its associated enhancement of recovery from physical and mental illness.